Experimental Study on Strength, Acoustic Emission, and Energy Dissipation of Coal under Naturally and Forcedly Saturated Conditions - Shen Wang; Huamin Li; Wen Wang; Dongyin Li; Weijie Yang (Advances in Civil Engineering)
Coal seam water injection (CSWI) is an effective technology that is widely used for preventing rock burst in coal mines. To deepen the understanding of the mechanism of CSWI to prevent rock burst, new equipment was designed to prepare forcedly saturated coal samples in this study and a series of mechanical experiments was conducted to investigate the mechanical properties, acoustic emission (AE), and energy dissipation characteristics of the coal samples in natural, naturally saturated, and forcedly saturated states. The experimental results show that the forced saturation treatment can significantly improve P-wave velocity and water content of coal samples, as water can penetrate more into micropores and fractures. The forced saturation method also significantly promotes the deformation capacity of the coal sample and reduces the strength by 83.37%. The main reason of the bearing capacity decrease for the forcedly saturated coal samples is plastic yielding rather than brittle crack propagation and slip. The derivative of the volumetric dissipation energy was proposed to evaluate the outburst proneness. The forced saturation method significantly reduces the risk of sudden release of energy and is more effective in preventing rock burst in coal seams than the natural saturation method.